Study guides

☆☆

Q: -4x plus 3y equals -2

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(2, 2)

You need to organise your question properly. 3x+2y=4 4x + 3y= 7? Is 4 4x = 44x or 4-4x or 4+4x How can there be 2 equal signs in 1 equation?

how do you use the substitution method for this problem 2x-3y=-2 4x+y=24

There are two simultaneous equations, so to solve for y, eliminate x: 1) 2x + 3y = 3 2) 4x - 3y = 9 Multiply equation (1) by 2 giving: 1) 4x + 6y = 6 2) 4x - 3y = 9 Next, subtract equation (2) from equation (1), giving: (4x - 4x) + (6y - -3y) = 6 - 9 → 9y = -3 → y = -1/3

Let's see. 2X + 3Y = 12 3Y = - 2X + 12 Y = -2/3X + 4 ---------------- 6Y - 4X = 2 6Y = 4X + 2 Y = 2/3X + 1/3 --------------------- Nope. They can't be. Plot a few points and see.

Related questions

(2, 2)

4x+3y = 6 3y = -4x+6 y = -4/3x+2 in slope intercept form

4x+3/3=y

You need to organise your question properly. 3x+2y=4 4x + 3y= 7? Is 4 4x = 44x or 4-4x or 4+4x How can there be 2 equal signs in 1 equation?

how do you use the substitution method for this problem 2x-3y=-2 4x+y=24

16x2 + 8x + 1 - 9y2 = (4x + 1)2 - (3y)2 which is a difference of two squares. = (4x + 1 + 3y)*(4x + 1 - 3y)

There are two simultaneous equations, so to solve for y, eliminate x: 1) 2x + 3y = 3 2) 4x - 3y = 9 Multiply equation (1) by 2 giving: 1) 4x + 6y = 6 2) 4x - 3y = 9 Next, subtract equation (2) from equation (1), giving: (4x - 4x) + (6y - -3y) = 6 - 9 → 9y = -3 → y = -1/3

Let's see. 2X + 3Y = 12 3Y = - 2X + 12 Y = -2/3X + 4 ---------------- 6Y - 4X = 2 6Y = 4X + 2 Y = 2/3X + 1/3 --------------------- Nope. They can't be. Plot a few points and see.

second equation x 2: 4x + 6y = 4 subtract first equation: 9y = 3 so y = 1/3 and x = 1/2

3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)

8x-3y=6-4x gives 12x-3y=6 which in standard form is y=-2+4x

x = 5 y = 2 4x - 3y = ? 4(5) - 3(2) = ? 20 - 6 = 14

People also asked